Influence of The Effectiveness of Hotel Tax, Restaurant Tax and Entertainment Tax Revenue on The Effectiveness of Local Revenue with Economic Growth As A Moderating Variable (Empirical Study on Districts/Cities in Jambi Province for the Period 2017-2023) - Samila, Putri; Sam, Iskandar; Safelia, Nela (Jurnal Cakrawala Akuntansi, 2025)
This study aims to determine the effect of the effectiveness of hotel tax, restaurant tax, and entertainment tax revenues on the effectiveness of local revenue (PAD) collection, with economic growth as a moderating variable in the Regencies/Cities of Jambi Province for the period 2017–2023. This study is a quantitative research using secondary data. The population in this study consists of Regencies/Cities in Jambi Province for the period 2017–2023. The sampling technique used is saturated sampling. A total of 77 data samples were examined in this study. Data analysis was conducted using multiple linear regression analysis and Moderating Regression Analysis (MRA), with IBM SPSS Version 29 as the analytical tool. The results of the study show that (1) the effectiveness of hotel tax revenue has no significant effect on the effectiveness of local revenue collection. (2) The effectiveness of restaurant tax revenue has a significant effect on the effectiveness of local revenue collection. (3) The effectiveness of entertainment tax revenue has no significant effect on the effectiveness of local revenue collection. (4) Economic growth is not able to moderate the effect of the effectiveness of hotel tax revenue on the effectiveness of local revenue collection. (5) Economic growth is not able to moderate the effect of the effectiveness of restaurant tax revenue on the effectiveness of local revenue collection. (6) Economic growth is not able to moderate the effect of the effectiveness of entertainment tax revenue on the effectiveness of local revenue collection.